THE TIMESCALE-DEPENDENT COLOR VARIABILITY OF QUASARS VIEWED WITH GALEX - Zhu(朱飞凡), Fei-Fan; Wang(王俊贤), Jun-Xian; Cai(蔡振翼), Zhen-Yi; Sun(孙玉涵), Yu-Han (The Astrophysical journal, 2016)
ABSTRACT In a recent work by Sun et al., the color variation of quasars, namely the bluer-when-brighter trend, was found to be timescale dependent using the SDSS band light curves in Stripe 82. Such timescale dependence, i.e., bluer variation at shorter timescales, supports the thermal fluctuation origin of the UV/optical variation in quasars, and can be modeled well with the inhomogeneous accretion disk model. In this paper, we extend the study to much shorter wavelengths in the rest frame (down to extreme UV) using GALaxy Evolution eXplorer (GALEX) photometric data of quasars collected in two ultraviolet bands (near-UV and far-UV). We develop Monte Carlo simulations to correct for possible biases due to the considerably larger photometric uncertainties in the GALEX light curves (particularly in the far-UV, compared with the SDSS bands), which otherwise could produce artificial results. We securely confirm the previously discovered timescale dependence of the color variability with independent data sets and at shorter wavelengths. We further find that the slope of the correlation between the amplitude of the color variation and timescale appears even steeper than predicted by the inhomogeneous disk model, which assumes that disk fluctuations follow a damped random walk (DRW) process. The much flatter structure function observed in the far-UV compared with that at longer wavelengths implies deviation from the DRW process in the inner disk, where rest-frame extreme UV radiation is produced.